2012
DOI: 10.1603/me11285
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Brown Widow and Black Widow Spiders (Araneae: Theridiidae) in Urban Southern California

Abstract: The brown widow spider, Latrodectus geometricus C. L. Koch, has become newly established in southern California during the first decade of the 21st century. Brown widows and egg sacs were collected within the urban Los Angeles Basin using timed searches. We also collected and compared the abundance and distribution of the native western black widow spider, Latrodectus hesperus Chamberlin & Ivie, to brown widows. Brown widows were very common around urban structures especially outside homes, in parks, under pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 11 publications
3
39
0
Order By: Relevance
“…All these considerations support the assumption that L. geometricus is in a great expansion of its distributional range, as was reported for others parts of the world (Garb et al 2004). Recently, Vetter et al (2012) reported the frequent presence of the brown widow spider in urban areas of southern California, USA, and the prevalence of this species in cities, around buildings, in greater numbers than the native black widow, Latrodectus hesperus Chamberlain & Ivie 1935, the latter being more common in natural and agricultural areas. Similarly, in Uruguay L. geometricus prevails in urban habitats in contrast to the native L. mirabilis which lives in grasslands under stones or in agricultural crops.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…All these considerations support the assumption that L. geometricus is in a great expansion of its distributional range, as was reported for others parts of the world (Garb et al 2004). Recently, Vetter et al (2012) reported the frequent presence of the brown widow spider in urban areas of southern California, USA, and the prevalence of this species in cities, around buildings, in greater numbers than the native black widow, Latrodectus hesperus Chamberlain & Ivie 1935, the latter being more common in natural and agricultural areas. Similarly, in Uruguay L. geometricus prevails in urban habitats in contrast to the native L. mirabilis which lives in grasslands under stones or in agricultural crops.…”
Section: Discussionsupporting
confidence: 82%
“…The urban habitats occupied by Latrodectus geometricus in Uruguay and the association of this species with synanthropic habitats are similar to that indicated to from other cities as windows frames and wall crevices in New Orleans and California in U.S.A. (Brown et al 2008, Vetter et al 2012 or under park benches in Yokohama, Japan (Ono 1995). At the same time the web architecture is similar to that described by Eberhard et al (2008).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Widows are well known in popular culture because of their neurotoxic venom (Jelinek 1997;Ushkaryov et al 2004), the tendency of several species to thrive in anthropogenically disturbed habitats (Trubl et al 2012;Vetter et al 2012), and because of their lurid reputation for females that kill and consume courting males (D'Amour et al 1936). In reality, there is a wide range of mating systems in this genus (e.g., Breene and Sweet 1985;Forster 1992;Andrade 1996;Knoflach and van Harten 2002;Segev et al 2003;Segoli et al 2006), ranging from polygyny and polyandry to the most extreme examples of male monogyny enforced by polyandrous female cannibals (observed in two species to date : Forster 1992;Segoli et al 2008a).…”
Section: Comparative Context and Variationmentioning
confidence: 99%